2017
DOI: 10.1213/ane.0000000000002095
|View full text |Cite
|
Sign up to set email alerts
|

Parecoxib Supplementation to Morphine Analgesia Decreases Incidence of Delirium in Elderly Patients After Hip or Knee Replacement Surgery: A Randomized Controlled Trial

Abstract: For low-risk elderly patients undergoing elective total hip or knee replacement surgery, multidose parecoxib supplemented to IV morphine decreased the incidence of postoperative delirium without increasing adverse events.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
64
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(68 citation statements)
references
References 35 publications
4
64
0
Order By: Relevance
“…Prolonged hospital stay, sleep deprivation and postoperative pain may all contribute to postoperative cognitive dysfunction. Minimising length of hospital stay by implementing fast‐track surgery, optimising postoperative pain control (in particular avoiding opioids ), and improving sleep hygiene might decrease early postoperative cognitive dysfunction. All relevant staff should receive training in the evaluation and management of pain in patients with cognitive impairment .…”
Section: Postoperative Cognitive Disordersmentioning
confidence: 99%
“…Prolonged hospital stay, sleep deprivation and postoperative pain may all contribute to postoperative cognitive dysfunction. Minimising length of hospital stay by implementing fast‐track surgery, optimising postoperative pain control (in particular avoiding opioids ), and improving sleep hygiene might decrease early postoperative cognitive dysfunction. All relevant staff should receive training in the evaluation and management of pain in patients with cognitive impairment .…”
Section: Postoperative Cognitive Disordersmentioning
confidence: 99%
“…All included studies were randomized controlled trials. In summary, 17 studies [12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28] described random sequence generation and allocation concealment. Nine studies [12-14, 20, 22, 24, 25, 27, 28] described the blinding of participants and personnel.…”
Section: Evaluating Literature Qualitymentioning
confidence: 99%
“…1 Increased postoperative pain has been associated with the occurrence of delirium and a previous randomizedcontrolled trial (RCT) investigating parecoxib, a selective cyclooxygenase-2 inhibitor, reduced the consumption of opioids and decreased delirium following total hip or knee replacement surgery. 2 Pregabalin is a structural analogue of c-aminobutyric acid. A meta-analysis of pregabalin for postoperative pain management found it may have a small opioid-sparing effect with a higher risk of serious adverse effects, but it is unclear if its opioid-sparing properties could also decrease postoperative delirium.…”
Section: To the Editormentioning
confidence: 99%
“…Despite the decreases in adjunct opioid utilization and better postoperative analgesia with pregabalin that we reported previously, our study found no effect of pregabalin on postoperative delirium following elective total hip arthroplasty. All patients received a selective cyclooxygenase-2 inhibitor perioperatively, which reduces postoperative delirium, 2 and thus may have nullified any effect of pregabalin. Other limitations of this analysis include a sample size powered for the original study's primary outcome; so we were likely underpowered to examine delirium in light of its unexpectedly lower incidence.…”
Section: To the Editormentioning
confidence: 99%